Calibration of Sr/Ca Ratio and In Situ Temperature Using Hawaiian Corals - Ryohei Uchiyama; Tsuyoshi Watanabe; Samuel E. Kahng; Atsuko Yamazaki (Geochemistry, Geophysics, Geosystems, 2023)
Abstract The Sr/Ca ratio of modern coral skeletons can record local seawater temperature (T) and is an important tool for reconstructing past environments. However, site‐specific calibrations are required to ensure accurate temperature reconstructions. Here, we examine three modern coral skeletons collected at contrasting sites on the island of Oahu, Hawaii to establish the first accurate calibrations for this region and investigate site specific influences on the calibration process. Satellite T data, which is used for many calibrations, may not be able to derive an accurate thermometer. For our shallow lagoonal sites, satellite T had smaller seasonal T ranges, which resulted in significantly higher slopes of Sr/Ca‐T compared to using in situ T. The traditional age model based on aligning only min/max values can lead to errors in the Sr/Ca‐T calibration due to variable growth rates. An enhanced age model which adds midpoint alignments between the min/max peak values can account for seasonal changes in growth rate and reduce the error. On the same island, site‐ and time period specific conditions can cause notable differences in the Sr/Ca‐T calibrations. The coral from an estuarine embayment showed a high Sr/Ca offset, likely due to high Sr/Ca in ambient seawater. For corals which experienced thermal stress, lower slopes were observed probably due to elevated Sr/Ca values during the period of thermal stress.